A administração de Saccharomyces boulardii THT 500101 altera a microbiota intestinal e reduz a hiperglicemia, dislipidemia e inflamação hepática em camundongos diabéticos induzidos por estreptozotocina - Albuquerque, Raquel Cristina Melo Ferreira De [UNIFESP] (2019)
The fasting hyperglycemia is considered a hallmark feature of diabetes mellitus (DM), and the loss of insulin production by the pancreatic β cells is caused by autoimmune antibodies that destroy these cells leading to type 1 diabetes mellitus. This metabolic disorder is associated with a number of complications including dysfunctions in organs such as kidneys, eyes, liver and heart, mainly due to hyperglycemia, oxidative stress and inflammation. Some of these changes appear to be associated with diabetic dyslipidemia, with high levels of triglycerides and low-density lipoproteins and lower levels of high-density lipoproteins. Saccharomyces boulardii is a probiotic capable of modulating the innate and adaptive immune system, reducing proinflammatory and activating anti-inflammatory responses. The aim of this study was to evaluate the hypothesis that streptozotocin-diabetic mice treated with Saccharomyces boulardii present improvement of glucose and triglycerides metabolism, reduction of liver inflammation concomitant with a beneficial impact in the gut microbiota profile. Male mice C57BL/6, received a single intraperitoneal injection of STZ (150mg/kg), and after 5 days the blood glucose was evaluated. It was considered diabetic the animal with blood glucose ≥ 250 mg/dl. The animals were distributed in 3 experimental groups (n = 6-12 / group): control (C), diabetes (D) and diabetes + probiotic (DP). The animals of treated groups received 300μl of S. boulardii (0,5x108 colony forming units –CFU/ml of yeast) by gavage, daily, during 8 weeks. Mice submitted to treatment presented reduced glycemia in comparison with diabetic group (D: 363 ± 21 vs. DP: 252 ± 36 mg/dL), which was correlated with an increase in C-peptide level (DP: 0,44 ± 0,1 vs. D: 0,0001 ± 0.0 ng/mL) and in hepatic glycogen content (DP: 16 ± 2 vs. D: 10 ± 0,9 mg/80g of wet tissue). Fat metabolism was significantly altered in STZ group, and Saccharomyces boulardii treatment regulated it, leading to a decrease in serum triglycerides secretion (D: 169 ± 10 vs. DP: 138 ± 7 mg/dL), increase in hepatic triglycerides storage (D: 5 ± 1,0 vs. DP: 13 ± 2,4 μmol/g) and modulation of inflammatory profile. Thus, considering the data presented here, we show up a possible potential therapeutic role of Saccharomyces boulardii for the treatment and attenuation of diabetes induced complications.